Heat stress decreased hair follicle population in rex rabbits. Issue 2 (28th December 2018) - Sun, Haitao; Zhang, Yin; Bai, Liya; Wang, Yuding; Yang, Liping; Su, Wenzheng; Gao, Shuxia
Abstract: The aim of this study was conducted to investigate the effect of heat stress on the hair follicle population and related signalling pathways in rex rabbits. Forty‐eight rabbits were randomly divided into two groups: one group in a high ambient environment (32 ± 2°C, heat stress) and the other group with normal temperature (20 ± 2°C, control). The results show that heat stress decreased the body weight gain and feed conversion rate, rabbit hair length and hair follicle density ( p < 0.05). Besides, heat stress suppressed the gene expression of noggin, insulin‐like growth factor 1 (IGF‐1) and IGF‐1 receptor and protein expression of phosphorylated mechanistic target of rapamycin (mTOR) in rabbit skin ( p < 0.05), while stimulated significantly the gene expression of bone morphogenetic protein 2 (BMP2) and BMP4 ( p < 0.05). Heat exposure did not alter significantly the gene expression of alkaline phosphatase, versican and hepatocyte growth factor compared with the control ( p > 0.05). In conclusion, noggin‐BMP, IGF‐1 and mTOR signalling pathways may be associated with the process of heat stress‐repressing hair follicle development.